PENGARUHBRANDEXPERIENCEDANBRANDIMAGETERHADAPBRANDLOYALTY MELALUIBRANDTRUSTSEBAGAIVARIABELINTERVENING (STUDIPADAPENGGUNAMASKAPAILIONAIRDIKOTASEMARANG) - Rosmauli Trifena; Wahyu Hidayat (Universitas Diponegoro, 2018)
This research caused by the development of business transporting , especially the air line route who that they are still needed by the community in Indonesia . This phenomenon characterized by abundance flight services as garuda indonesia, lion air, citilink, sriwijaya air, batik air and many more. Lion Air became one of theairline by offering lowcostandmostattractive to the community , hasbeenproven bytopbrand index20122016 to the second position after garuda indonesia. However, there were fluctuations on 2012-2016 and last year a decline in the number of passengers in Semarang City on 2016 . This research aims to determine the effect of brand experience and brand image on brand loyalty through brand trust as intervening variable of lion air airline. The type of this research is explanatory research, with data collection techniques through The questionnaire. Using the technique of sampling with purposive sampling. Sample in this research were 112 respondent consists of Lion Air Airline Users in Kota Semarang. The Technique to collect data in this research through the questionnaire. This research use qualitative analysis technique and quantitative analysis technique. Quantitative analysis use validity test, realibility test, correlation coefficient, simple and multiple regression analysis, determination coefficient, signification test that Being tested use SPSS for Windows. The results showed that there are positive effect of brand experience to brand trust, positive effect of brand image to brand trust, positive effect of brand experience to brand loyalty, positive effect of brand image to brand loyalty, positive effect of brand trust to brand loyalty, positive effect of brand experience to brand loyalty through brand trust as intervening variable, and positive effect of brand image to brand loyalty through brand trust as interveningvariable.